The Status of Sea Turtles in Indonesia) - Ismu Sutanto S; Ating Somantri; J P Schulz (Department of Forest Resources Conservation and Ecotourism - IPB University, 1989)
Evaluation of sea turtles in Indonesia was based on the suggestion of the Directorate General of PHPA to WWF/IUCN, to collect accurate data about sea turtle populations and their habitats in the Indonesian islands, as the basic data for the formulation of the Sea Turtle Conservation Strategy inIndonesia.Rewlh of the exploration activities on the hlands of Sumatera, Java, Bali, Kalimantan, Sulawesi and Maluku showed that illegal egg collection and hunting especidy of the hawksbill and green turtles stiU happened almost in all locations. Many nesting beaches had remained damaged vegetations due to the invation of human settlements. Nevertheless, we still have enough time to formulate the sea turtle conservation strategy, to save the sea turtle populations and their habitats on several islands.